Hybrid Intuitionistic Fuzzy Set–TOPSIS with a New Similarity Formula: Non-Medical Healing Factors of Covid-19 Patients (European Journal of Pure and Applied Mathematics, 2026)
The formula of similarity measure by Yafie Song et.al. is one of the many formulas that have been developed by the previous authors. Numerically, it is better than other formulas. In this article, we propose a hybrid Intuitionistic Fuzzy Set (IFS)-TOPSIS method by using the similarity measure of Yafie Song. Then, we used the method to determine the most influential non-medical healing factors of Covid-19 patients using that method as case study. The subject of this research is Covid-19 patients in East-Java, Indonesia. Our result shows that “one-house family” is the most influential factor of the non- medical healing for Covid-19 patients.
Keywords: Intuisionistic Fuzzy Sets; Similarity; TOPSIS